Built to Last or Meant to End: Intertemporal Choice in Strategic Alliance Portfolios - Bakker, Rene M.; Knoben, Joris (Organization Science, 2015)
Asalient but rarely explicitly studied characteristic of interfirm relationships is that they can intentionally be formed for finite periods of time. What determines firms’ intertemporal choices between different alliance time horizons? Shadow of the future theorists suggest that when an alliance has an explicitly set short-term time frame, there is an increased risk that partners may behave opportunistically. This does not readily explain the high incidence of time-bound alliances being formed. Reconciling insights from the shadow of the future perspective with nascent research on the flexibility of temporary organizations, and shifting the focus from the level of individual transactions to that of strategic alliance portfolios, we argue that firms may be willing to accept a higher risk of opportunism when there are offsetting gains in strategic flexibility in managing their strategic alliance portfolio. Consequently, we hypothesize that environmental factors that increase the need for strategic flexibility—namely, dynamism and complexity in the environment—are likely to increase the relative share of time-bound alliances in strategic alliance portfolios. Our analysis of longitudinal data on the intertemporal alliance choices of a large sample of small and medium-sized enterprises provides support for this argument. Our findings fill an important gap in theory about time horizons in interfirm relationships and temporary organizations and show the importance of separating planned terminations from duration-based performance measures.